Metabolic syndrome and the urinary microbiome of patients undergoing percutaneous nephrolithotomy - Ryan A. Dornbier; Chirag P. Doshi; Shalin C. Desai; Petar Bajic; Michelle Van Kuiken; Mark Khemmani; Ahmer V. Farooq; Larissa Bresler; Thomas M.T. Turk; Alan J. Wolfe; Kristin G. Baldea (Asian Journal of Urology, 2024)
Objective: To identify possible stone-promoting microbes, we compared the profiles of microbes grown from stones of patients with and without metabolic syndrome (MetS). The association between MetS and urinary stone disease is well established, but the exact pathophysiologic relationship remains unknown. Recent evidence suggests urinary tract dysbiosis may lead to increased nephrolithiasis risk. Methods: At the time of percutaneous nephrolithotomy, bladder urine and stone fragments were collected from patients with and without MetS. Both sample types were subjected to expanded quantitative urine culture (EQUC) and 16 S ribosomal RNA gene sequencing. Results: Fifty-seven patients included 12 controls (21.1%) and 45 MetS patients (78.9%). Both cohorts were similar with respect to demographics and non-MetS comorbidities. No controls had uric acid stone composition. By EQUC, bacteria were detected more frequently in MetS stones (42.2%) compared to controls (8.3%) (p=0.041). Bacteria also were more abundant in stones of MetS patients compared to controls. To validate our EQUC results, we performed 16 S ribosomal RNA gene sequencing. In 12/16 (75.0%) sequence-positive stones, EQUC reliably isolated at least one species of the sequenced genera. Bacteria were detected in both “infectious” and “non-infectious” stone compositions. Conclusion: Bacteria are more common and more abundant in MetS stones than control stones. Our findings support a role for bacteria in urinary stone disease for patients with MetS regardless of stone composition.